Stroke Prevention and Cognitive Reserve: Emerging Approaches to Modifying Risk and Delaying Onset of Dementia - Willis, Kevin; Hakim, Antoine M. (Frontiers in Neurology, 2013)
Demographic changes and improvements in health care are projected to result in dramatic increases in the prevalence of dementia. Alzheimer’s disease is widely considered to be the primary cause of dementia - a disease for which there is currently no cure nor effective treatment, and for which it is thought that little can be done to mitigate risk. However, an increasing understanding of the role and extent of vascular contributions to the development of dementia, and appreciation of the interactions between stroke and Alzheimer’s disease, suggest that targeting vascular risk factors may be very beneficial in reducing the impact of dementia. We also describe how active stimulation of the brain throughout the life course builds cognitive reserve that can offset or compensate for cognitive decline in later life. Finally, we discuss the implications of these emerging approaches for dementia prevention and advocate for the urgent implementation of more extensive public health strategies to improve vascular health.